Brazilian derivatives and securities : pricing and risk management of FX and interest-rate portfolios for local and global markets /: pricing and risk management of FX and interest-rate portfolios for local and global markets. (2016) - Carreira, Marcos; Brostowicz, Richard J
No abstract available